Knowledge, Attitudes, and Practices of HIV-Positive Adolescents Related to HIV/AIDS Prevention in Abidjan (Côte d'Ivoire) - Azagoh-Kouadio Richard; Yeboua Kossonou Roland; Yao Kouassi Christian; Kouassi-Kouadio Amenan Cécile; Aholi Jean Michel; Cissé Lacina; Asse Kouadio Vincent (Hindawi Limited, 2020)
Introduction. In sub-Saharan Africa, many adolescents living with HIV adopt behaviors and practices at risk of transmitting this infection. The aim of the study was to assess the knowledge, attitudes, and practices of HIV-positive adolescents regarding the transmission of HIV for the prevention of this disease. Methods. Knowledge Attitude Practical Survey (KAP) conducted from June 20 to August 22, 2018 in pediatrics at the University Hospital of Treichville. It included consenting HIV-positive adolescents followed up in the voluntary testing counseling unit. The variables studied related to sociodemographic aspects, knowledge, attitude, and practice relating to the transmission of HIV. The analysis was descriptive. Results. The active queue was 349 children, including 210 adolescents. Fifty adolescents (22 boys and 28 girls) participated in the study, a participation rate of 24%. The average age of the participants was 16 years (extreme 10 and 19 years). The respondent was an orphan (38%), a secondary school (58%), and separated living parents in 42%. He stated that he did not know he was infected in 62%, and that he had sex with at least one partner in 54%. He knew the modes of transmission and the means of prevention in 72% of the cases. He knew that an HIV-positive adolescent could transmit the disease in 68%, and that HIV/AIDS was incurable in 40%. 42% of respondents said that an infected person on ARVs was contagious. Twenty-nine respondents who had a partner said they had unprotected sex in 58%. All of the adolescents surveyed said that they did not talk to friends and family about HIV. Conclusion. The level of knowledge, attitude, and practice of HIV-positive adolescents regarding HIV/AIDS transmission is insufficient. We suggest setting up a therapeutic HIV/AIDS education program for these adolescents.